Direct bilayer growth: a new growth principle for a novel WSe2 homo-junction and bilayer WSe2 growth. Issue 6 (29th January 2020) - Fang, Long; Yuan, Xiaoming; Liu, Kunwu; Li, Lin; Zhou, Peng; Ma, Wei; Huang, Han; He, Jun; Tao, Shaohua
Abstract : Homo-junction and multi-layer structures of transition metal chalcogenide (TMD) materials provide great flexibility for band-structure engineering and designing photoelectric devices. Abstract : Homo-junction and multi-layer structures of transition metal chalcogenide (TMD) materials provide great flexibility for band-structure engineering and designing photoelectric devices. However, the knowledge of van der Waals epitaxy growth limits the development of these heterostructures. Herein, we employed the chemical vapor deposition (CVD) growth strategy to synthesize novel WSe2 homo-junction samples with a triangular monolayer in the center and three AA stacking bilayer flakes connected to the vertexes of the monolayer. The emitted photon energy from the bilayer near the junction showed a blueshift in energy of up to 24 meV compared with bare bilayer WSe2, confirming the charge transfer effect from monolayer to bilayer WSe2 . Further growth studies revealed the shape evolution from WSe2 homo-junction to bilayer. The whole homo-junction formation and evolution process cannot be explained by the traditional layer-by-layer growth mechanism. Instead, a direct bilayer growth approach is proposed to explain the bilayer formation and evolution at the vertexes of the bottom layer of WSe2 . These findings suggest that the growth of bilayer TMDs is more complex than our previous understanding. This work presents deepens insight into van der Waals epitaxy growth, and thus is valuable for guiding the fabrication of novel homo-junctions for both fundamental science and optoelectronic applications.